Reference values for hand grip strength in Japanese community-dwelling elderly: a meta-analysis - Kamide, Naoto (Environ Health Prev Med, 2015)
OBJECTIVES: Reference values for hand grip strength in Japanese community-dwelling elderly independent in activities of daily living (ADLs) were calculated by meta-analysis. METHODS: Papers reporting data on hand grip strength in elderly Japanese adults ≥60 years of age and independent in ADLs were retrieved from electronic databases. Data were extracted from the selected papers and the weighted mean for hand grip strength by sex was calculated by random effect model. The association of hand grip strength with age and body weight was also analyzed using meta-regression analysis. RESULTS: Data for 15,784 individuals (5216 men and 10,568 women; mean age 67.0–79.8 years) were extracted from 97 sets of data from 33 papers. The weighted mean for hand grip strength was calculated as 33.11 kg [95 % CI 32.27–33.96] in men and 20.92 kg [95 % CI 20.45–21.39] in women. A significant negative correlation was also seen between hand grip strength and age. CONCLUSIONS: The mean hand grip strength of elderly people calculated in this study can be used as a reference value for the hand grip strength of Japanese community-dwelling elderly who are independent in ADLs. However, age needs to be considered in reference values for hand grip strength.